Cochabambia Pirán, 1959 (Hemiptera: Heteroptera: Acanthosomatidae), a senior homonym of Cochabambia Marcuzzi, 1985 (Coleoptera: Tenebrionidae), with notes on the placement of Cochabambia Pirán - Faúndez, Eduardo I.; Rider, David A.; Carvajal, Máriom A. (Zootaxa, 2014)
Cochabambia Marcuzzi (1985) (Coleoptera: Tenebrionidae) is a junior homonym of Cochabambia Pirán, 1959 (Hemiptera: Heteroptera: Acanthosomatidae). Allotriocochabambia is proposed as a new name for the tenebrionid genus, and as result Allotriocochabambia kulzeri (1985) is proposed as new combination. The placement of Cochabambia Pirán within the Acanthosomatidae is discussed.